How To Use Poster To Teach English - Ni Made Purnami Widyawati (ID Solutions, 2021)
the aimed of this article is to develop learning media, namely poster. because poster will drive student motivation and character in learning English. The students conducted this article because there were problems in learning, the students have to understand to knowledge and have skills in learning. Students must also have good character in increasing learning motivation. So that the author makes posters to gave students improve to learn because posters in education was make students to improve student learning. These poster as a media are common among the learner and student were easy to learn, particularly in the current condition, students have to build ideas and develop knowledge through written writing. so that in this writing the poster was chosen to be used as material to develop student creativity in class learning and theauthor chose a Canva application to make learning applications to serve as classes learning materials. This research was used qualitative method with DnD model namely design, development, and evaluation. The population of this research was the English teacher SMPN 4 Kintamani with a sample all seven grade students with 32 students who were sampled in this study. the results of using these three steps can help teachers to use posters in teaching English and the results of the posters can be used as material for teaching in class.